2003
DOI: 10.1590/s0037-86822003000400003
|View full text |Cite
|
Sign up to set email alerts
|

Ovos e órgãos reprodutores de fêmeas de Angiostrongylus costaricensis são reconhecidos mais intensamente por soros humanos de fase aguda na angiostrongilíase abdominal

Abstract: O Angiostrongylus costaricensis é um nematódeo intra-arterial de roedores. O homem acidentalmente pode se infectar ao ingerir alimentos ou água contaminados. Nosso objetivo foi o de descrever as estruturas do parasita que são reconhecidas por soros humanos das fases aguda e convalescente da angiostrongilíase abdominal. O método de imunofluorescência indireta foi empregado para estudar a reatividade sobre ovos íntegros e cortes de vermes fêmeas e de larvas de primeiro estágio (L1). L1 também foram estudadas ínt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 9 publications
0
10
0
7
Order By: Relevance
“…This parasitic disease has been reported throughout Central and South America (Morera & Cespedes 1971, Incani et al 2007, Palominos et al 2008. In endemic areas, such as the southern region of Brazil, epidemiological and clinical features are used as diagnostic indications of AA (Agostini et al 1983, 1984, Ayala 1987, Graeff-Teixeira et al 1991, Bender et al 2003, Mesen-Ramirez et al 2008, Ben et al 2010, Abrahams-Sandi et al 2011. However, AA is a disease with unspecified clinical manifestations.…”
mentioning
confidence: 99%
“…This parasitic disease has been reported throughout Central and South America (Morera & Cespedes 1971, Incani et al 2007, Palominos et al 2008. In endemic areas, such as the southern region of Brazil, epidemiological and clinical features are used as diagnostic indications of AA (Agostini et al 1983, 1984, Ayala 1987, Graeff-Teixeira et al 1991, Bender et al 2003, Mesen-Ramirez et al 2008, Ben et al 2010, Abrahams-Sandi et al 2011. However, AA is a disease with unspecified clinical manifestations.…”
mentioning
confidence: 99%
“…Ancylostoma/Necator, Toxocara and Schistosoma are examples of parasites whose eggs have proven useful in the serological diagnosis of the disease (Zaman & Singh 1965, Glickman et al 1978, Khalil et al 1989, Alarcón de Noya et al 2000. In 2003, Bender et al (2003 described the high antigenicity of A. costaricensis eggs and, in 2008, Mesén-Ramírez et al (2008 demonstrated the usefulness of a crude extract of this antigen in the development of an ELISA test. However, in the latter study, one of the main problems was the high number of eggs required to prepare the antigenic extract.…”
Section: Discussionmentioning
confidence: 99%
“…The ELISA developed in that study showed higher sensitivity but lower specificity than the serological tests that are based on the A. costaricensis crude antigen. Bender et al (2003), in a study with human sera and using indirect immunofluorescence, reported that A. costaricensis eggs display high antigenicity and low cross-reactivity when used as the antigen. Furthermore, observations from experimental animal models have also shown the importance of eggs in the humoral response during an A. costaricensis infection (Geiger et al 1999, Abrahams-Sandi et al 2004.…”
mentioning
confidence: 99%
“…Comparing to the data obtained by Caetano (2005) and Ohbayashi & Takeuchi (2007), the weight and height average shell were lower than those obtained by this, as compared to Albuquerque (2003) the average obtained were higher. The specimen large and strong presence, probably with sexual development complete reflects the process of invasion of the species in Salvador, with the occupation of urban ecosystems, not only causing serious ecological and economical problems, but also possible damages to human and domestic animals health (Teles et al 1997, Vasconcellos & Pile 2001, Raut & Barker 2002, Bender et al 2003, Thiengo et al 2006, Thiengo et al 2007, Thiengo et al 2008.…”
Section: Aspects Of Population Dynamics Of Achatina Fulicamentioning
confidence: 99%